-48+(-10)=

Simple and best practice solution for -48+(-10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -48+(-10)= equation:


Simplifying
-48 + (-10) = 0
-48 + -10 = 0

Combine like terms: -48 + -10 = -58
-58 = 0

Solving
-58 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (x-6)(x-6)(3)=108 | | (x-6)(x-6)=108 | | 7(2y-3)-(5y+7)= | | 8x^3-5x^2=72x-45 | | 1.31x=5.24 | | 7x+22=y | | 9y^3=-9y^2+10y | | 5x-2(x-4)=10(x-2) | | 8+5(4+4)-6= | | 7x-5=7x+3 | | 3(a+1)=7(a-9) | | 10x+15y=5 | | 5x+8y=49 | | 10x+15y=5(x+y) | | x^2-99x-2=0 | | e^7x+1=14 | | 8y^2-3y+5y^2-4y= | | (6-2)4+2(8-5)= | | 3p^2-5p-28=0 | | h^2=6h+16 | | 5x=3x-5 | | -3t^3=-11t^2-20t | | 20v^2=7v+3 | | T-21=14 | | (k+5)(k-1)=-8 | | 3p^3-75p=3p^2-75 | | 10x+5=23 | | 3z^4=3z^2 | | x^4+28=11x^2 | | 2b+3a= | | 9x+30=2x^2 | | 9c+6= |

Equations solver categories